Heat Stability of Concentrated Milk Systems Kinetics of the Dissociation and Aggregation in High Heated Concentrated Milk Systems - Dumpler, Joseph (Springer Fachmedien Wiesbaden : Spektrum, 2018)
In his study, Joseph Dumpler proves a strong correlation between the dry matter content of the milk concentrate and the maximum temperature-time combinations for the heat treatment of concentrated skim milk without visible coagulation. The author also states that direct heat treatment is superior to indirect heat treatment for preservation of liquid milk concentrates or decontamination of concentrated milk before spray drying. Contents Heat Stability of Concentrated Milk Heat-Induced Coagulation of Concentrated Milk Heated by Direct Steam Injection Dissociation and Coagulation of Caseins and Whey Proteins Modelling of Heat Stability and Heat-Induced Aggregation of Casein Micelles Mechanistic Aspects of Heat-Induced Coagulation Target Groups Lecturers and students of dairy science and technology, food science and processing Practitioners and suppliers of processing equipment in the fields of dairying, food processing, food process engineering The Author During his PhD, Joseph Dumpler was employed as a scientific officer at the Chair Food and Bioprocess Engineering at the TUM School of Life Sciences Weihenstephan of the Technical University of Munich. His research was focused on the heat stability and heat treatment of concentrated milk by direct steam injection technology.